ADDIE Model Application for Development of Teaching Material Based on Flipped Learning for Lecturer’s in Polytechnic - A. Jalil, Nor Azyani; Madar, Ahmad Rizal; Kassim, N. I (Journal of Social Transformation and Regional Development, 2021)
The process of teaching and learning is an important element of ensuring that students are able to keep up with the content of the subject being presented. In order to attract studentâ€™s interest and improve the student’s academic achievement, the process of learning should be a fun and challenging process for students’ thinking. The main issue of this study is that science and mathematics learning for some students are abstract and difficult to understand. This study aims at the development of teaching material based on flipped learning in Polytechnic. The findings of this study show that the development of teaching materials based on flipped learning involves all phases of ADDIE model namely analysis, design, development, implementation, and evaluation. In this study, the teaching of flipped learning materials produced has gained the content of five experts in teaching and learning. The results show that the researcher has successfully produced teaching material that emphasizes the five main components of the active learning method, namely Jigsaw Puzzle, video presentation, Bingo Balls of Doom, Group Presentation, and Assignment Assessment. It is hoped that the development of teaching materials based on these flipped learning methods will enhance students’ academic achievement and achievement and enable students to work together to make the learning process more meaningful.